Faktor Lingkungan Yang Berkaitan Dengan Kejadian Malaria (Studi Di Wilayah Kerja Puskesmas Kepil I Kabupaten Wonosobo Tahun 2004) - Ginandjar, Praba; Hidayati, Hidayati; Gambiro, Gambiro (Jurnal Kesehatan Lingkungan Indonesia, 2005)
ABSTRACT Background: Malaria is one of disease caused by intracellular parasite called Plasmodium and transmitting by Anopheles spp mosquito. Area of Kepil I Local Government Clinic in Wonosobo District is one of malaria endemic area with 32.28‰ annual parasite incidence (API). Environmental factors included physical, biological and social influence the transmission of malaria. Objective: Analyzing environmental factors related to malaria occurrence in area of Kepil I Local Government Clinic. Method: This was a case control study. Participant of this study divided into two groups i.e. case and control group, each consisted of 70 subjects. As case group was malaria patients of Kepil I, taken by systematic random sampling technique, while control group was case’s nearest neighbor with same sex, similar age and economic status, and not suffering of malaria. Data was analyzed by chi-square test and odds ratio (OR). Result: Statistical analysis showed that the occurrence of malaria related to house condition (p=0.041), using of mosquito repellent (p=0.020), stall distance (p=0.005) and night outdoor activity (p=0.001), while closing doors and windows (p=0.194), using bed net (p=0.091), cattle existence (p=0.089) and night outdoor bathe, wash and defecation habit (p=0.168) had no correlation with malaria occurrence in area of Kepil I Local Government Clinic. OR value showed that risk of malaria increase 2.167 times in house with unclose wall and roof, 3.160 times in subject that not use mosquito repellent at night, 4.829 times in subject living in a house with integrated stall or the distance less then five meters, and 4.244 times in subject with night outdoor activity. Conclusion: Environmental factors related to malaria in area of Kepil I Local Government Clinic were unclose wall and roof of the house, not using mosquito repellent at night, existence of stall that is integrated with house or the distance is less than five meters and night outdoor activity. Keywords: malaria, physical environment, biological environment, social environment